Religiosity and Religious Commitment in the Consistency of Student Worship Practices: An Analysis of Religious Psychology - Fazrah Ainun Nisa; Andini Indah Hasanah; Esa Nur Cahyani; Surawan Surawan (Yayasan Cendekia Gagayunan Indonesia, 2026)
The consistency of students’ worship practices often fluctuates even though they possess adequate religious understanding. This condition indicates that cognitive understanding of religion alone does not necessarily guarantee stable religious behavior. This study aims to analyze the relationship between religiosity and religious commitment with the consistency of students’ worship practices, as well as to examine the simultaneous influence of these variables from the perspective of the psychology of religion. The study employed a quantitative approach using an explanatory research design. The sample consisted of 50 students selected through purposive sampling. Data were collected using a Likert-scale questionnaire and multiple linear regression with the assistance of SPSS software. The results show that religiosity and religious commitment have a strong relationship with the consistency of students’ worship practices and simultaneously have a significant influence with a contribution of 48.3%. These findings indicate that the consistency of students’ worship practices is not only influenced by the level of religiosity but also by religious commitment that encourages the internalization of religious values in daily life.